Green Human Resource Management Practices in the Hotel Industry: Ethiopian Perspective - Chimedessa, Sintayehu Gurmessa; Chawla, Arvinder Singh (Gyan Management Journal, 2024)
This article’s primary focus is on the application of green HRM  techniques by the hotel sector. Every subordinate and the  management bodies must be committed to making the organization  green. Nowadays, the larger picture of human resource management  is examined in light of sustainability. The degree of application  was examined by identifying and evaluating six key GHRM item  components. Green employee empowerment and participation, green  training and development, green performance management and  appraisal, green reward and compensation, and green management  of organizational culture were the highlighted GHRM practices.  The degree and scope of green HR practices are evaluated using an  exploratory research design. For this study, data from both primary  and secondary sources were compiled. In order to update and validate  the list of fundamental GHRM practices that had previously been  found through literature reviews, input and suggestions from aspiring  HR managers were now critically needed. According to the findings,  the overall GHRM practice implementation is 2.07, which is regarded  as a low level. Moreover, the statistical outcome indicates that workers  are receiving compensation and benefits for their contributions even in  the lack of appropriate eco-friendly hiring, training, and development  guidelines. The results of statistical analysis indicated a strong positive  correlation between environmental performance and the six green  HRM practices.
Keywords: Environmental Performance; Green Human Resources Management; Hotel Industry